Mengenal Bubur Kampiun, Bubur Manis Khas Padang - Febryola Indra; Vincentia Nayla Kosasih; Sherla Valensky (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
Indonesian porridge has become one of the most recognized foods in Indonesia, even for foreign tourists. Bubur is usually known as a salty dish. But do you know the sweet version of bubur? Padang City is one of the largest cities in Indonesia with a total area of 694.96 km². Geographically, Padang is located on the west coast of Sumatra Island and is the capital of West Sumatra Province. Not only known for its many folklores such as Malin Kundang, Padang culinary is also widely known. Padang rice is one of them. Even Padang rice has attracted the interest of culinary connoisseurs in Australia. Padang rice itself is a rice dish eaten with several side dishes, such as rendang, cakes, pop chicken, curry chicken, balado eggs, cassava leaves, skin crackers, and many more. In addition to Padang rice, the sweet porridge menu (bubur kampiun) as a dessert is also one of the food menus from Padang that is certainly worth trying. Bubur Kampiun is one of Padang's specialties, precisely in the mainland Minangkabau (Darek) area, Bukittinggi, West Sumatra. Porridge that has a sweet and legit flavor along with a soft texture, making this dish popular especially during Ramadan for breaking the fast, party events, and in the morning as an alternative to the breakfast menu.